A Framework Of Efficient Interim Payment For Public Construction Projects In Kano State, Nigeria - Umar, Garba Maiunguwa (2020)
Inefficiency in interim payment leads to late and non-payment situations which will affect the contractors and project performance. Late and non-payment situation is seen as normal or ‘acceptable’ condition in Nigeria. This ill condition must be rectified because it has many negative effects such as cost overrun, project delay, reduce profit and growth, disputes and project abandonment. This research proposes a framework of efficient interim payment focusing on public projects in Kano State, Nigeria using open system theory and efficiency concept.